A mononuclear Co(ii) complex formed from pyridinedimethanol with manifold slow relaxation channels. Issue 33 (2nd August 2017) - Valigura, Dušan; Rajnák, Cyril; Moncol, Ján; Titiš, Ján; Boča, Roman
Abstract : A mononuclear hexacoordinate complex [Co(pydm)2 ](dnbz)2 formed from 2, 6-pyridinedimethanol in the coordination sphere of Co(ii ) and dinitrobenzoato anions exhibits magnetic anisotropy of an easy axis type and a field induced slow magnetic relaxation. Abstract : A mononuclear hexacoordinate complex [Co(pydm)2 ](dnbz)2 formed from 2, 6-pyridinedimethanol in the coordination sphere of Co(ii ) and dinitrobenzoato anions exhibits magnetic anisotropy of an easy axis type and a field induced slow magnetic relaxation with manifold relaxation channels. The low-frequency relaxation time is as slow as τ LF = 0.13 s at B DC = 0.4 T and T = 1.9 K.